MODEL REGULASI PENYELENGGARAAN PEMILIHAN KEPALA DAERAH (PILKADA) SECARA BERSAMA (Studi tentang Model Regulasi Penyelenggaraan Pemilihan Kepala Daerah Gabungan di Jawa Timur Tahun 2008) - HIDAYAT, YURISTIARSO (2011)
The reformation occurred in 1998 has transformed the Indonesian political system. Particularly, the transformation has shifted the political party system from tri parties (Golkar, PPP, PDI) to multi-parties. The transformation automatically leads to the system of conducting directly presidential or district heads elections. Regarding the election of district heads, this system is expected to be able to improve the local political system. Though, in reality, this system causes several problems. They are abusive process of elections, violence of political competition, apathies among people, and funding. The above problems then make a lot of people think. They view that the election can be conducted collectively. This idea is basically to avoid the people's apathies due to the frequently conducted elections and to reduce the KPUD's burden in facing many problems. Therefore, this study is intended to investigate the regulation model of collective election of district heads in East Java. This study is qualitative in nature, normative, descriptive, and explanatory. This approach aims at reconstructing and describing a phenomenon qualitatively. The techniques of data collection used are literature reviews, interviews, and observations. The data analysis is carried out in a normative-qualitative way in the form of synchronization stages and laws-based findings. Also, data verification and interpretation are hermeneutically undertaken. The findings show as follows. First, the collective election of district heads in East Java is an ideal model, which can be used in other places. This model has complete rules which are used by the KPUD Jatim. Secondly, the laws used to underlie the national or local policies to conduct collective elections of district heads include UU No.32 Tahun 2004, PP No. 6 Tahun 2005, Permendagri No. 21 Tahun 2005, dan Surat Edaran Menteri Dalam Negeri, Nomor 121.35/1681/2008.